PERAN CORPORATE GOVERNANCE DALAM MEMODERASI PENGARUH STRUKTUR MODAL, COMPANY AGE DAN FIRM SIZE TERHADAP PROFITABILITAS PERBANKAN (Studi Pada Perbankan yang Terdaftar di BEI Tahun 2015-2021) - Amilia Kharisma Putri; Irene Rini Demi Pangestuti (Jurnal Akuntansi dan Pajak, 2023)
Profitability is the result of all company activities or activities which are a benchmark for the success of a company. Profitability information can be seen through financial reports. Efforts to obtain good profitability certainly require corporate governance, with the reason being that companies with good corporate governance will be preferred by investors and creditors, because corporate governance has a supervisory function within the company, so that the interests of managers and owners of the company will both be achieved. This study aims to examine how the role of corporate governance plays a role in moderating the influence of capital structure proxies debt to equity ratio, company age and firm size on profitability (ROA) in banks listed on the IDX in 2015-2021. The method used in this research is quantitative with secondary data. Pparentln salmpel dilalkukaln listenln purposive method salmpling, criterialThe sample for this study are (a) Banking companies listed on the Indonesia Stock Exchange for 2015-2021, (b) Banking companies on the Indonesia Stock Exchange publish complete financial reports for 2015-2021.The research analysis tool uses the SPSS 25.00 software with the method Moderated Regression Analysis (MRA). The results of the study showed that there was a significant negative effect on the debt to equity to profitability (ROA) with siq. of 0.000 (H1 accepted). There is a significant negative effect company age to profitlbillils siq.of 0.000 (H2 rejected). There is a significant positive effect on firm size to probability sig. of 0.000 (H3 accepted). There is a significant influence debt to equity ratio to profitability is moderated laudit committee siq value. of 0.046 (H4 accepted). Company age has no significant effect to profitability with moderation audit committee siq. of 0.202 (H5 rejected). There is a significant effect of firm size to profitability moderated audit committee siq. of 0.046 (H6 accepted). In the feasibility f-test of the first equation model, the calculated f-value is 56.904 with a sig. 0.000. The f-test of the second equation has an f-count value of 31.326 with a sig.0.000 value. Equation 1 determination test resultsvalue (adjusted R²) of 0.501, debt to equity ratio, company age andfirm size can explain Profitability (ROA) of 50.1% and the remaining 49.9%. The 2-value equation termination test (adjusted R²) after moderation of 0.521 means that the variation of the variable debt to equity ratio, company age,firm sizeand the audit committee can explain Profitability (ROA) of 52.1% and the remaining 47.9% is explained by other variables outside of this study. Keywords: Debt To Equity Ratio,Companyages, Firm Sizeand Profitability Audit Committee (ROA)